Sustainable management of paddy crop residues: effects on methanotrophs diversity and value for soil health restoration. (16th June 2021) - Singh, Chhatarpal; Tiwari, Shashank; Rai, Pradeep Kumar; Singh, Jay Shankar
Abstract: In recent years, improved paddy crop varieties, advanced tools and technologies have resulted in a huge quantity of crop residues (CRs) production. Hence, appropriate sustainable management of the paddy CRs produced annually is needed. In this study, a field experiment was conducted to evaluate the impact of rice husk biochar (RHB) amendments on soil physico‐chemical characteristics, methanotrophs diversity, and functional pmoA genes numbers in paddy soil. The pmoA gene (27 kDa) encodes the β‐subunit of the particulate methane monooxygenase ( pMMO ), an enzyme responsible for methane oxidation found in most of the methanotrophs. A marked variation in methanotrophs diversity, functional pmoA genes abundance, and physico‐chemical parameters in paddy soil have been noted across the given amendments. The RHB significantly improves soil physico‐chemical status and enhances methanotrophs community structure and number of pmoA gene numbers in paddy soils. The various soil physico‐chemical parameters were improved due to RHB + microbial inoculant treatments. Maximum rice grain yield (5.91 ± 0.07 t ha −1 ) and methanotrophic functional pmoA gene numbers (57.25 ± 0.88 × 10 7 g −1 paddy soil) were found in the RHB + microbial inoculant treated plot compared to untreated (control) plot. The predominant methanotrophic bacteria identified by the denaturing gradient gel electrophoresis (DGGE) in RHB treated paddy soils were Methylovulum and Methylobacter members of the Methylococcaceae family. Consequently, the methanotrophs community study based on DGGE analysis shows that RHB could be a beneficial amendment to increase the methanotrophic community composition in paddy soils. Overall, the results suggest that the RHB amendment could markedly enhance soil conditions and methanotrophs abundance via regulating soil physico‐chemical properties in nutrient‐deprived and degraded paddy agriculture soils.